MENINGKATKAN HASIL BELAJAR PERMAINAN BOLA VOLI MELALUI METODE KELOMPOK BERMAIN (Department of Physical Education, Sport, Health and Recreation, 2014)
This study aims to determine the improvement of learning outcomes through methods volleyball game groupplay on fourth grade students of SDN 02 Pantianom Olean District Pekalongan. This study uses classroomaction research was conducted in two cycles of the Cycle I and Cycle II.From the results of research conducted, found that student achievement had peningkatakan from the initialconditions to the first cycle to the second cycle, both from an increase in the average value of learning the gameof volleyball as well as the value of mastery learning outcomes. The average value of learning outcomes in theconditions of the first cycle of 70.52%, 80.98% and Cycle II, so the average increase student learning outcomesfrom the first cycle to the second cycle was 10.46%. Ability volleyball game this penjas students in learning hasincreased quite high. Conclusions from this research is the use of group play can improve learning outcomes inthe high jump style straddle fourth grade student Olean 02 Patianom District Pekalongan in the AcademicYear 2012-2013.